PENGARUH PROFITABILITAS, BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK, DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Hakim, Ilham Taufiqul; Maryama, Siti (JURNAL EKONOMI, 2024)
This study aims to analyze the effect of Profitability, Deferred Tax Expenses, Tax Planning, and Corporate Governance on Firm Value in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The population in this study amounted to 35 companies and the number of samples was 175 samples with the sampling method using purposive sampling. The data analysis technique uses Descriptive Statistical analysis, Classical assumption test, Hypothesis testing and Multiple linear regression. The results of the analysis in this study indicate that Profitability, Deferred Tax Expenses, and Corporate Governance have a positive and significant effect on Company Value while Tax Planning has a negative and significant effect on Company Value. In the F-test it is known that Profitability, Deferred Tax Expenses, Tax Planning, and Corporate Governance simultaneously affect Firm Value. The coefficient of determination is 0.457, which means that 45.7% of the Company’s value is influenced by these variables, while the remaining 54.3% is influenced by other variables. These results indicate that there are still other variables outside the study that can explain Firm Value.